Distinctive disease subgroups according to differentiation stages in adult patients with T‐cell acute lymphoblastic leukemia. (26th February 2013) - Shimizu, Hiroaki; Handa, Hiroshi; Hatsumi, Nahoko; Takada, Satoru; Saitoh, Takayuki; Sakura, Toru; Miyawaki, Shuichi; Nojima, Yoshihisa
Abstract Objectives The categorization of T‐cell acute lymphoblastic leukemia (T‐ALL) into four subgroups according to the degree of thymic differentiation was proposed in 1995, and this categorization scheme has been described in the World Health Organization classification 4th edition with minor changes. The aim of this study is to explore the clinical significance of leukemia cell differentiation stages in patients with T‐ALL. Methods We analyzed 36 adult T‐ALL patients, including six patients (17%) in pro‐T stage, 16 (44%) in pre‐T stage, three (8%) in cortical‐T stage, and 11 (31%) in medullary‐T stage. Pro‐T and pre‐T stages were arbitrarily clustered as the immature group, and cortical‐T and medullary‐T stages as the mature group. Results Patients in the immature group had unique presentations, including lower lactate dehydrogenase levels, lower frequency of mediastinal tumor, and higher expression of myeloid antigens than the mature group. There was no difference in the treatment strategies between both groups. Although patients in the immature group had a lower complete remission (CR) rate when compared with the mature group (45% vs. 79%, respectively; P = 0.04), the 3‐yr overall survival (OS) for both groups was comparable (27% vs. 38%, respectively; P = 0.66). Such discrepancy between the CR rates and the OS could be partially explained by survival benefit of allogeneic transplantation observed in the immature group but not in the mature group. Conclusions These findings indicate that T‐ALL patients can be categorized into two biologically distinctive subgroups according to the differentiation stages, and this stratification might enable prospective identification of patients with poor chemotherapy response.